High Steel (Brown Tint) (2006)
Colour Rick Boland (writer), Mary Walsh (writer/director), Ron Hynes (music), Christa Borden, Phil Churchill, Steve Cochrane, Johnny Harris, Amy House, Joel Thomas Hynes, Alison Woolridge Resource Centre for the Arts (RCA)